2015
DOI: 10.1016/j.orggeochem.2015.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal maturation on plant-derived terpenoids and leaf wax n-alkyl components

Abstract: Plant biomarkers, such as terpenoids and leaf wax components (n-alkanes, n-alkanoic acids and nalkanols), are frequently found in sediments and can be used, often in association with stable carbon (and hydrogen) isotope measurements, as paleovegetation and paleoclimate proxies. However, few controlled studies have monitored plant biomarker alteration to determine if certain plant biomarkers are preferentially lost relative to more recalcitrant forms.To investigate the role of selective alteration and degradati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 60 publications
3
21
0
Order By: Relevance
“…Upon heating and increasing maturity, n-alkane δ 13 C values appear to not be altered up to the pre-oil generation window. This was determined with hydrous pyrolysis experiments using fresh leaves from Acer rubrum (red maple), Platanus occidentalis (American sycamore), Pinus sylvestris (Scots pine) and Taxodium distichum (bald cypress) at various temperatures (Diefendorf et al, 2015c). In that study, changes in long chain n-alkane δ 13 C values were not observed until hydrous pyrolysis temperatures increased to 250 ºC and above.…”
Section: Plant Wax Alteration and Diagenetic Fatementioning
confidence: 90%
See 1 more Smart Citation
“…Upon heating and increasing maturity, n-alkane δ 13 C values appear to not be altered up to the pre-oil generation window. This was determined with hydrous pyrolysis experiments using fresh leaves from Acer rubrum (red maple), Platanus occidentalis (American sycamore), Pinus sylvestris (Scots pine) and Taxodium distichum (bald cypress) at various temperatures (Diefendorf et al, 2015c). In that study, changes in long chain n-alkane δ 13 C values were not observed until hydrous pyrolysis temperatures increased to 250 ºC and above.…”
Section: Plant Wax Alteration and Diagenetic Fatementioning
confidence: 90%
“…For immature sediments, n-alkanoic acids and n-alkanols are polymerized to insoluble macromolecules through diagenetic alteration. Evidence for this polymerization and formation of kerogen comes from extensive use of confined and hydrous pyrolysis experiments using fresh leaf or arthropod tissue (Stankiewicz et al, 2000;Gupta et al, 2007a;Gupta, 2014;Diefendorf et al, 2015c) and from observations made on fossils (e.g., Mösle et al, 1997Mösle et al, , 1998. For immature sediments and rocks, nalkanes appear to be rather immobile.…”
Section: Plant Wax Alteration and Diagenetic Fatementioning
confidence: 99%
“…Above 330–360 °C an increasing depletion in 12 C takes place, which can be attributed to the cleavage of 12C-12C bonds [155]. On the other hand, Diefendorf et al [156] report a shift of compound-specific n -alkane δ 13 C values up to 2 ‰ in either direction depending on species and chain length, at a temperature higher than 200–250 °C. Thus, a shift in the compound-specific n -alkane δ 13 C values would corroborate that BL and WL represent in fact burning if all other parameters are ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…At significantly higher thermal exposure within the realm of gas generation, previous studies have shown that thermal cleavage affecting longer n-alkane compounds could increase the δ 13 C values of residual long-chain n-alkanes by up to 4‰ (Clayton & Bjorøy, 1994;Odden et al, 2002;Tang et al, 2005), due to the preferential breakage of 12 C-12 C bonds that leave remaining structures enriched in 13 C (Andresen et al, 1995;Lewan, 1986;Sackett, 1978). The temperatures based on our T max represent early oil generation (Riber, 2009), well below those that would alter alkane 13 C compositions by loss due to thermally driven cracking by more than 1‰-2‰ (Diefendorf et al, 2015). Because the sampled section is within a similar level of thermal maturity, approximately early oil-window, and thus thermal effects, if present, were similar across all samples.…”
Section: Thermal Maturity Effect On the δ 13 C Of N-alkanesmentioning
confidence: 89%